2004
DOI: 10.1117/12.514229
|View full text |Cite
|
Sign up to set email alerts
|

Relating the morphology of a poly(p-phenylene vinylene)/methanofullerene blend to bulk heterojunction solar cell performance

Abstract: Few techniques are available where the morphology of blends can be determined in all three dimensions on a nanometer scale. Here we describe the use of a combination of techniques to resolve the morphology both laterally and vertically in spin cast films of a poly(p-phenylene vinylene)/methanofullerene blend. These blends are used as photoactive films in plastic bulk heterojunction solar cells where the performance strongly depends on the molecular morphology. In addition to depth profiling by dynamic time-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…3d. In both figures, we observe very pronounced trends, which can be correlated with different morphology regimes of the polymer-PCBM blend 27 , schematically represented in Fig. 3c.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…3d. In both figures, we observe very pronounced trends, which can be correlated with different morphology regimes of the polymer-PCBM blend 27 , schematically represented in Fig. 3c.…”
Section: Resultsmentioning
confidence: 75%
“…When increasing x beyond 70%, regime (3), phase separation occurs, creating separate regions dominated by singlecarrier electron and hole currents. The exact concentration at which this happens for our blends is known from the literature 27 , but has also been verified by means of atomic force microscopy (see Supplementary Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of V OC in Figure 6 maybe does not attribute to variation of PCBM concentration in the mixture of BHJ layer. Studies on MDMO-PPV:PCBM devices showed that the V OC was composition independent for PCBM contents above about 10% by weight [21]. For organic BHJ materials, the general perception is that V OC is determined by the energy difference between the HOMO of the donor and the LUMO of the acceptor [15].…”
Section: External Photocurrent Quantum Efficiency Spectramentioning
confidence: 99%
“…A BHJ is usually obtained by relying on the phase separation (on the nanometer scale) of donor and acceptor materials in a mixed layer, where insufficient phase separation often compromises the device performance owing to carrier recombination and poor charge transport [21]. In general, and as a result of phase separation on the nanometer scale occurring in the active layer blend, the donor/acceptor interfaces (photoactive p-n heterojunction sites) spread within the entire volume of the BHJ composite layer.…”
Section: External Photocurrent Quantum Efficiency Spectramentioning
confidence: 99%